FOMO AND GEN Z INVESTMENT BEHAVIOR: A QUALITATIVE STUDY ON EMOTIONAL BIAS IN FINANCE - Faris Ramadhan; Etty Sri Wahyuni; Adnan Suhardis; Robin; Sumantri (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This qualitative study investigates how Fear of Missing Out (FOMO) influences Generation Z investment behavior and emotional bias in financial decision-making processes. The research employed an interpretive phenomenological approach with in-depth semi-structured interviews conducted among Generation Z investors in Indonesia to understand the psychological mechanisms underlying FOMO-driven investment decisions. Systematic thematic analysis revealed three primary themes: FOMO as an emotional investment driver, social media influence creating information asymmetry, and financial literacy functioning as a complex moderating factor. The findings demonstrate that FOMO operates as a powerful emotional compulsion that systematically overrides rational decision-making processes, with social media exposure to peers' investment success serving as the most potent trigger for impulsive investment behavior. A significant "information paradox" emerged where participants heavily rely on low-credibility sources such as financial influencers while underutilizing high-credibility alternatives like official company reports, prioritizing accessibility over accuracy. The relationship between financial literacy and FOMO vulnerability proved non-linear, with medium literacy levels paradoxically increasing overconfidence bias while high literacy enabled sophisticated rationalization of emotional decisions. These findings contribute to behavioral finance theory by revealing how digital-social contexts amplify emotional biases beyond traditional market psychology models, suggesting that conventional financial education approaches may be insufficient for addressing emotionally-driven decision-making among digital-native generations.